Integrating Batik Ghentongan Tanjung Bumi Madura into Science Education: Development of Student Response Instrument - Wiwin Puspita Hadi; Aida Fikriyah (Mitra Edukasi dan Publikasi, 2026)
Batik Ghentongan Tanjung Bumi Madura, as a representation of local cultural wisdom, offers meaningful potential for contextual integration into science education. The aim of this research was to analyze the validity and reliability of an instrument designed to assess student responses to Batik Ghentongan Tanjung Bumi Madura. The study was conducted in Tanjungbumi Subdistrict, Bangkalan Regency, East Java, Indonesia, involving 248 junior high school pupils, including of 119 males and 129 females, selected through simple random sampling. A quantitative survey design was employed using 8 items on a 4 point Likert scale. Data were analyzed using common factor analysis and the Rasch model with Winsteps software version 4.7.0.0. The results show that 6 items met the validity criteria, while 2 items require revision; the raw variance explained by measures reached 24 percent, indicating acceptable unidimensionality, and the Cronbach Alpha value of 0.95 demonstrates excellent internal consistency reliability. In conclusion, the instrument is adequate valid and reliable for identification students’ responses to Batik Ghentongan Tanjung Bumi Madura, although further refinement of several items is recommended to strengthen construct validity and improve measurement precision. This study contributes to Sustainable Development Goal 4, Quality Education, and Sustainable Development Goal 8, Decent Work and Economic Growth, by promoting culturally responsive science learning and strengthening awareness of local cultural industries as a component of sustainable economic development.